Analisis Efektifitas Program Promosi Kesehatan dalam Mencegah Diare pada Balita Diwilayah Kerja Puskesmas Miran - Epi Dusra; Ety Dusra; Herlien Sinay; Lutfi Latuconsina; Amelia Kairoty (Journal Pharma Saintika, 2023)
Diarrhea is defecation with liquid stools or: half liquid (half solid), water content greater than 200 grams or 200m1/24 hours Another definition of diarrhea is feces with a thinner consistency and more frequent frequency (>2x in one day).The purpose of this study was to analyze the effectiveness of health promotion programs in preventing diarrhea in toddlers in the work area of the Miran Health Center The research method used by this researcher is a type of qualitative research Desaín this research is field research (feld re.search) this research uses key informants, namely the head of the miran health center, the main informant is the mother of a toddler who has diarrhea and supporting informants, namely the diarrhea program holder at the miran health center. Data collection procedures are carried out through interviews (interviews). The implementation of diarrhea programs in the work area of the miran health center has been well implemented The results of the evaluation obtained the number of toddlers with diarrhea in the work area of the miran health center is 12 toddlers and there are further assistance and intervention measures for diarrhea cases with the hope that it can reduce the rate of diarrhea in the work area of the miran health center.